Efectos del cambio climático y las variaciones del nivel del mar sobre la vegetación costera de Chiapas, México durante el Holoceno medio y tardío - Bocanegra Ramírez, Dulce María (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
The Chiapas Coast is extended by the Mexican South Pacific, where there are located several lagoon-estuary systems, which are sensible to climatic changes as at the same time where converge the rain waters coming from the mountain range waters and the marine waters. An important factor to considerate in this coast zone is the occurrence of extreme events such as torments and tsunamis. In this work, a paleoambience reconstruction was made from two extracted nucleus of the coast zone, one form de La Joya Lagoon (2.75 m depth) and the other from de El Ciegón estuary (2 m. depth). Climate changes and variations of the sea level were examined during the middle and the late Holocen, using a multi-proxi focus based on pollen analysis, estratigraphy, organic and inorganic charcoal, magnetic susceptibility and isotopic geochemistry analysis. The obtainded results show that the oscillations of the sea level starting from the middle Holocen modified the composition of the vegetation in La Joya Lagoon and El Ciegón estuary with the aportation of salad water to those sites, indicate that in 1300 years cal b.P. occurred the closure of the La Joya Lagoon stoping the salad water aportation, and in the El Ciegón was stabilized the manglar vegetation at the same time. These results indicate that if the contemporary climatic changing continues, the sea level would rise provocation the migration and a possible extinction of the manglar vegetation in the site. In the La Joya Lagoon the sedimentation shows high energy events attributed to climatic changes during the middle Holocen (7100-4000 years cal BP). In the Chiapas coast was registered the appearance of early human occupation between 7100 and 6350 years cal BP, based on the presence of the Cucurbitaceae pollen.

La costa de Chiapas se extiende por el Pacífico Sur Mexicano, donde se localizan varios sistemas lagunares-estuarinos, los cuales son sensibles a cambios climáticos y a su vez son sitios donde convergen las aguas de escorrentía y las aguas marinas. Un factor importante a considerar en esta zona costera es la ocurrencia de eventos extremos como tormentas y tsunamis. En el presente trabajo se realizó una reconstrucción paleoambiental a partir de dos núcleos extraídos de la zona costera, uno de la laguna La Joya (2.75 m de profundidad) y el otro del estero El Ciegón (2 m de profundidad). Se analizaron los cambios climáticos y las variaciones del nivel del mar durante el Holoceno medio y tardío, utilizando un enfoque multi-proxy basado en análisis polínico, estratigrafía, carbón orgánico e inorgánico, susceptibilidad magnética y geoquímica isotópica. Los resultados obtenidos muestran que las oscilaciones del nivel del mar a partir del Holoceno medio modificaron la composición de la vegetación en la laguna La Joya y el estero El Ciegón con el aporte de agua salada a los sitios, indican que a los 1300 años cal a.P. ocurrió el cierre de la laguna La Joya impidiendo el aporte de agua marina, y en El Ciegón se estabilizó la vegetación de manglar en el mismo tiempo. Estos resultados indican que de continuar el cambio climático contemporáneo, aumentaría el nivel del mar provocando la migración y una posible extinción de la vegetación de manglar en el sitio. En la laguna La Joya la sedimentación muestra eventos de alta energía atribuidos a cambios climáticos durante el Holoceno medio (7100-4000 años cal a.P.). En la costa de Chiapas se registró la aparición de ocupación humana temprana entre los 7100 y los 6350 años cal a.P. en base a la presencia del polen de Cucurbitaceae.
Instituto de Investigación en Metalurgia y Materiales. Maestría en Geociencias y Planificación del territorio
Keywords: info:eu-repo/classification/cti/1; IIMM-M-2014-1225; Zona costera; Cambios climáticos; Holoceno; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5220